CT ventilation imaging derived from breath hold CT exhibits good regional accuracy with Galligas PET. Issue 2 (May 2018) - Eslick, Enid M.; Kipritidis, John; Gradinscak, Denis; Stevens, Mark J.; Bailey, Dale L.; Harris, Benjamin; Booth, Jeremy T.; Keall, Paul J.
Abstract: Background and purpose: CT ventilation imaging (CTVI) derived from four dimensional CT (4DCT) has shown only moderate spatial accuracy in humans due to 4DCT image artefacts. Here we assess the accuracy of an improved CTVI using high quality exhale/inhale breath-hold CT (BHCT). Materials and methods: Eighteen lung cancer patients underwent exhale/inhale BHCT, 4DCT and Galligas PET ventilation scans in a single imaging session. For each BHCT and 4DCT scan, we performed deformable image registration (DIR) between the inhale and exhale phase images to quantify ventilation using three published metrics: (i) breathing induced lung density change, CTVI DIR - HU (ii) breathing induced volume change CTVI DIR - Jac and (iii) the regional air-tissue product, CTVI HU Spatial accuracy was reported as the voxel-wise Spearman correlation r between CTVI and Galligas PET. Results: For BHCT-based CTVIs ( N = 16), the CTVI DIR - HU, CTVI DIR - Jac and CTVI HU methods yielded mean (range) r values of 0.67 (0.52–0.87), 0.57 (0.18–0.77) and 0.49 (0.14–0.75) respectively. By comparison the 4DCT-based CTVIs ( n = 14) had values of 0.32 (−0.04 to 0.51), 0.16 (−0.31 to 44) and 0.49 (0.20–0.77) respectively. Conclusions: High quality CT imaging is a key requirement for accurate CT ventilation imaging. The use of exhale/inhale BHCT can improve the accuracy of CTVI for human subjects.